2002
DOI: 10.4314/wsa.v28i3.4903
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium removal from aqueous solution by ion-exchange using packed bed natural zeolite

Abstract: Ammonium removal from aqueous solution by a natural ion-exchange resin was investigated by considering the factors affecting the ammonium-exchange capacity including the zeolites' particle size, the loading flow rates and the impact of a number of regenerations upon the ion-exchange capacity. The resin column was exhausted by downflow at 10, 25, 50 and 75 bed volume (BV)/h, until effluent ammonium concentration of more than 10 mg/l NH 4 + was achieved. The results indicate that conditioning of the zeolite impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 7 publications
5
77
2
6
Order By: Relevance
“…Demir and coworkers (Demir et al 2002) studied the capacity of Bigadiç clinoptilolite for removing ions from synthetic aqueous solutions under varying conditions. The actual ion-exchange capacity of the conditioned fi ne and coarse clinoptilolite was found to be 0.57 and 0.38 mg/g zeolite, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Demir and coworkers (Demir et al 2002) studied the capacity of Bigadiç clinoptilolite for removing ions from synthetic aqueous solutions under varying conditions. The actual ion-exchange capacity of the conditioned fi ne and coarse clinoptilolite was found to be 0.57 and 0.38 mg/g zeolite, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…By choosing suitable filter media, high purification efficiency of constructed wetlands can be achieved. Laboratory column and batch experiments have been performed with zeolites to assess their sorption of ammonium nitrogen (Papadopoulos et al, 1996;Demir et al, 2002). Moreover, attention has been paid to the potential use of industrial byproducts in constructed wetlands and other wastewater-treatment systems.…”
Section: Introductionmentioning
confidence: 99%
“…The tests results on conditioned zeolite showed that the cation exchange capacity was 10.06 (in breakthrough point) and 18.38 mg NH 4 + g -1 zeolite as total capacity (6,8). The results indicated that high level of regeneration (95-98%) might be achieved with solution of ClNa (table 1).…”
Section: Characterization Of Clinoptilolitementioning
confidence: 78%
“…Clinoptilolite is a natural zeolite that has been known for their ability to remove ammonium from polluted waters. The capacity of zeolite and chemical regeneration for ammonium removal was investigated in several studies [3][4][5][6][7][8]. Usually, the service cycle is a down flow packed bed column followed by chemical regeneration (usually by NaCl).The major drawback of this process is the high cost of the chemical regeneration stage and disposal of the concentrated ammonium-sodium brain produced [9].…”
Section: Introductionmentioning
confidence: 99%